COMMUNITY'S OPTIMISM IN THE UTILIZATION OF KARST AREA IN THE FRAMEWORK OF AGRARIAN REFORM (STUDY IN PUCUNG VILLAGE, GIRISUBO DISTRICT, GUNUNG KIDUL DISTRICT) - Nugroho, Aristiono (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Pucung Village, Girisubo District, Gunung Kidul Regency, is located in a karst area which requires a certain method to make the best use of it. The karst area, which is often considered by some people in other areas as an obstacle, is actually considered a blessing by the community and the Pucung Village Government. This attitude arose as part of the optimism of the community and the Pucung Village Government in the karst area within the framework of agrarian reform. This study uses qualitative research methods, with a rationalistic approach. The number of informants was 10 people, who were selected purposively. The data consists of: (1) Primary data, obtained from interviews with informants; (2) Secondary data, in the form of Pucung Village population data. Meanwhile, data analysis was carried out by utilizing Qualitative Analysis Techniques. The results of this study indicate that the optimism of the community and Pucung Village Government in the utilization of the karst area within the framework of agrarian reform is manifested in the form of: First, the seriousness of the community and Pucung Village Government, when collaborating with the National Land College (STPN) to carry out participatory research activities and community empowerment ; Second, the sincerity of the community and the Pucung Village Government when working hard to develop agriculture, animal husbandry, small businesses and tourism; Third, the seriousness of the community and the Pucung Village Government when carrying out repairs and arrangements for physical, intellectual, human, financial and technological facilities; Fourth, the seriousness of the community and Pucung Village Government, when improving people's welfare independently and peacefully by utilizing the iconic potential of Pucung Village, namely: Bengawan Solo Purba; Fifth, the seriousness of the community and Pucung Village Government when carrying out land use and utilization activities.